La vicepresidencia en América como desafío a la democracia representativa: los casos de Estados Unidos, Brasil y Argentina - Sribman Mittelman, Ariel (El Colegio de México A.C., 2021)
Since the Third Wave of democratization, political science has extensively debated the performance of the presidential model in Latin America and its effects on democratic stability. However, that debate has ignored a key figure: the vice presidency. The objective of this article is to reflect on this position, which exists practically throughout the Americas, as a challenge to the representative character of democracy, in connection with the existing debate on presidentialism and the political stability of American democracies. Based on three cases—Brazil, Argentina and the United States—this article considers the fixed character of the role (not removable by the president) and the mechanisms provided for his election as factors that diminish the representative character of the vice presidency and lead to instability and a lack of legitimacy of the Executive. Drawing on these factors, this article concludes there is a need to introduce reforms to the vice presidency, or consider its replacement by another mode of succession.